Nutrient Composition of Arugula Leafy Greens Following Application of Ascorbic Acid Foliar Sprays - Shivani Kathi; He Liu; Haydee Laza; Leslie Thompson; Sukhbir Singh; Wei Li; Catherine R. Simpson (Horticulturae)
Agronomic biofortification of vitamin C is a promising strategy to address vitamin C deficiencies in populations that lack access to diverse and nutritious diets. Different application methods can improve the vitamin C content in various crops; however, foliar application of ascorbic acid (AA) solutions has been under-explored. To determine if spray concentration, number of applications, and day of harvest would affect vitamin C in arugula leafy greens, foliar sprays consisting of 100 ppm and 200 ppm of AA and deionized (DI) water control were applied. Treatment application was initiated during the baby-leaf stage and subjected to a total of three sprays over the course of the experiment, followed by harvest at two days and four days after spraying (DAS). The harvested plants were measured for fresh and dry biomass and analyzed for vitamin C content, mineral composition, chlorophyll levels, and carotenoid content. The results of this study demonstrated a notably elevated total vitamin C concentration (p = 0.0002) and AA content (p = 0.02) in arugula leaves treated with a 200 ppm AA spray following the third application and harvested at 4 DAS. Additionally, the AA application improved the fresh and dry weight of leafy greens but did not exhibit any significant variances regarding the mineral composition of P, K, Ca, Mg, S, B, Zn, Mn, and Fe. Alternatively, AA foliar sprays reduced Cu content in leaves suggesting that AA reduced Cu accumulation in arugula leafy greens. In summary, the findings of this study establish that the foliar application of 200 ppm AA is an effective approach for increasing the vitamin C content in arugula leafy greens while improving the plant’s biomass, mineral composition, and stress responses. These biofortified arugula leafy greens exhibit the potential to offer plant protection against environmental stresses and a more consistent supply of vitamin C to humans upon consumption.